THE CONTRIBUTION OF PESANTREN IN EMPOWERING THE PEOPLE'S ECONOMY (Analytical Study of Islamic Boarding Schools in Indonesia) - Sugianto, Sugianto; Hafifuddin (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2025)
Pesantren have been an important part of the history of Islamic education in Indonesia since the 14th century AD. In addition to functioning as centers of religious education, pesantren also play a strategic role in economic and social empowerment. This research uses a qualitative method, by applying descriptive analysis research type. Descriptive analysis research is a method used as a framework for thinking to obtain research results. This research is included in the library research area, where researchers analyze the contribution of pesantren in the economic empowerment of the people. This research uses primary data from book references and scientific articles using the Publish or Perish application tool. The results of the study found; first, since the 14th century AD, pesantren were established as centers of Islamic education, preaching, and people's struggle. In the 17th century, Sultan Agung gave special attention to pesantren to create a conducive learning environment; second, the role of pesantren in supporting the welfare of the people through education, economy, and social; third, developing an integrated economic empowerment model based on cooperation and waqf-based economic programs. The findings of this study confirm that pesantrens have great potential in improving the economic independence and welfare of the people